Metode Dakwah Penceramah di Komunitas Yuk Ngaji Solo - Latif Ghufron Aula; Zainul Abas (UIN Raden Mas Said Surakarta, 2020)
The existence of technological developments,in the end, makes all information easily accessible. Likewise with the youth lifestyle, one of which is in the city of Surakarta, whether it refers to the proper use of technology according to the times, or vice versa, falling into a wrong path. This is a challenge for the Yuk Ngaji community to direct youth towards positive and beneficial things. This study aims to describe the da'wah method by preachers in the Yuk Ngaji Community to encourage youth hijrah in Surakarta. The method used in this study was a qualitative descriptive method by describing phenomena in the field through data collection and Instagram social media. The data collection technique was carried out through observations, interviews, and documentation. This study found that the da'wah method by preachers in Yuk Ngaji Community to encourage youth hijrah in Surakarta was by using bill hikmah and mauidhah hasanah. The da'wah method carried out by the preachers using the bil hikmah method was carried out by identifying the conditions of the da'wah target, making the study interesting and making comfortable for youth congregations to follow. Furthermore, the mauidhah hasanah da'wah method was carried out through preachers who deliver the material subtly so that it can move the hearts of the youth to be able to practice it in everyday life.